Griffiths like robust ferromagnetism in Co3-xMnxTeO6; (x = 0.5, 1, 2). (August 2016) - Singh, Harishchandra; Ghosh, Haranath; Prajapat, C.L.; Singh, M.R.
Graphical abstract: Highlights: We present Co 3-x Mn x TeO6 (CMTO; x  = 0.5, 1, 2) as the potential magnetic material. Coexistence of ferromagnetic (FM) and antiferromagnetic (AFM) interaction is shown. Inverse magnetic susceptibility shows robust Griffiths phase like FM correlation. Very large effective magnetic moment leads to the nano size FM domains in CMTO. Both FM as well as AFM phases is sensitive to the content of Co/Mn ratio. Abstract: We report near room temperature ferromagnetic (FM) as well as low temperature antiferromagnetic (AFM) correlations in Co 3-x Mn x TeO6 (CMTO); ( x  = 0.5, 1, 2) solid solutions, using thorough DC magnetization studies. For all x, CMTO shows not only short-range robust FM order ∼185 K, but also long range enhanced AFM order ≤45 K. Griffiths-like FM interactions show up in magnetization data; it exists over an extended temperature range and remains unsuppressed in magnetic field as large as 1 T, indicating its robustness. Variations in both FM and AFM phases as a function of Mn concentration also support our observation of anomalous behavior in the average bond distances and charge states (JAP 116: 074904 (2014)). Further, an attempt towards the structural insight into the observed complex magnetic behavior by using network like structural analysis has been drawn. These observations make CMTO an interesting magnetic system from fundamental and application perspectives.